Analisis Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening di PT XYZ - Albany, Rifka Aulia; Waluyo, Minto (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effect of the relationship between organizational culture and job satisfaction on employee performance, with organizational commitment as a mediator. This study uses the Structural Equation Model with the Partial Least Square (SEM-PLS) methodology. The results of this study conclude that the organizational culture variable does not significantly affect organizational commitment at PT XYZ; however, the job satisfaction variable has a positive and significant effect on organizational commitment at PT XYZ. The organizational culture variable does not significantly affect employee performance at PT XYZ; however, the job satisfaction variable has a positive and significant effect on employee performance at PT XYZ. The organizational commitment variable has a positive and significant effect on employee performance at PT XYZ. However, the organizational commitment variable cannot strengthen or weaken the effect of organizational culture on employee performance at PT XYZ. The organizational commitment variable can strengthen or weaken the effect of the job satisfaction variable on employee performance at PT XYZ.